Vývoj motorů BMW - Süttő, Daniel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Táto bakalárska práca s názvom „Vývoj motorů BMW“, pojednáva o histórií vzniku lietadlových motorov a motorov pre jednostopové vozidlá závodu BMW. Poskytuje prehľad konštrukčných riešení a vývoja motorov v období od roku 1916 do roku 1969.

This bachelor thesis called “The development of BMW engines” deals with the history of the genesis of aircraft engines and the engines of single-track vehicles of the BMW factory. It shows a survey of constructive solutions and the development of engines in the period from 1916 to 1969.
Development of BMW engines
Keywords: Motor; BMW; lietadlový motor; motocykel; výkon; zdvihový objem motora; valec.; Engine; BMW; aircraft engine; motorcycle; power; engine cylinder capacity; cylinder.